Active Tectonics and Earthquake Geology Along the Pallatanga Fault, Central Andes of Ecuador - Baize, Stéphane; Audin, Laurence; Alvarado, Alexandra; Jomard, Hervé; Bablon, Mathilde; Champenois, Johann; Espin, Pedro; Samaniego, Pablo; Quidelleur, Xavier; Le Pennec, Jean-Luc (Frontiers in Earth Science, 2020)
Based on new geological data and the analysis of a 4-m spatial resolution Digital Elevation Model (DEM), we provide a detailed and comprehensive description of section of the Chingual Cosanga Pallatanga Puna Fault System, a major active fault system in Ecuador. This work allows estimating new slip rates and large earthquakes parameters (displacement, recurrence) along a ~100 km-long section of the continental-scale dextral shear zone that accommodates the extrusion of the North Andean Sliver with respect to the South America continental Plate. We focus on the NE-SW Pallatanga strike-slip fault zone and related contractional and transcurrent features that extend to the north in the Inter-Andean valley and the Cordillera Real, respectively. The detailed analysis of the available DEM allowed mapping a series of lineaments at the regional scale and along the entire fault system. Field studies on key areas show valley deflections, aligned and elongated hills of Tertiary or Quaternary sediments, as well as faulted Holocene deposits and even preserved coseismic free-face ruptures in some places. Such morphological anomalies strongly suggest that those landscape scars represent long-living (Holocene to historical times) earthquake faults. Altogether, these new data confirm that very large crustal earthquakes (M~7.5) have been generated along the fault system, probably during multiple segment ruptures. This conclusion agrees with reports of large earthquakes during historical times (post 1532 CE) in 1698, 1797 and 1949. They all occurred in the vicinity of the Pallatanga fault, causing catastrophic effects on environmental and cultural features. Based on new sample dating of both soils and volcanic series, we infer that the NE-SW dextral Pallatanga fault slips at rates ranging from ~2 to ~6 mm/yr for southern and central strands of the studied area, respectively. Further north, surface faulting is distributed and the deformation appears to be partitioned between sub-meridian fault-related folds (~2 mm/yr) and NE-SW strike-slip fault(s), like the ~1 mm/yr Pisayambo Fault that ruptured the surface in 2010. All this information offers the opportunity to size the earthquake sources for further seismic hazard analyses.